Psychologycal Symptoms of Cooping with Chronic Pain in Adolescent Girls – A Pilot Study - Horvat Rauter, Barbara; Groleger Sršen, Katja (Anali PAZU HD, 2022)
Chronic pain is a recurrent pain that persists beyond the expected normal time of healing, lasting three months or longer. The prevalence of chronic pain in children is about 30%. Longer lasting coping with chronic pain leads to different psychological, social consequences and school absenteeism. The aim of our paper is to establish and investigate psychological consequences of chronic pain in 10 adolescent girls with the average age 14.9 years (SD = 1.9). All of them were examined by the physical and rehabilitation medicine specialist, meet criteria for chronic pain. We assessed their current psychological wellbeing through self-evaluation (The Revised Children’s Anxiety and Depression Scale – RCADS, Fear of Pain Questionnaire - FOPQ, The catastrophizing scale –PCS) and parent reported behaviour (CBCL). The adolescent girls reported separation anxiety and more pronounced depression symptoms. They more often avoid physical activity, deal with emotions of fear and think about pain increase through activity. Anxiety and depressive symptoms, somatisation, difficulties in social relationships and copping with stress. We conclude that all participants deal with psychological consequences of chronic pain. The awareness of psychological consequences in long term chronic pain and a detailed assessment are crucialfor planning further psychological treatment and therapy.